Little Fire, Zygmunt! You are a Guest and I am a Guest… Conceptualization of Fire as a Living Creature in the Polish Folk Culture. An Ethnolinguistic Analysis - Szadura, Joanna (Vilnius University Open Series, 2020)
The analysis is focused on the reconstruction of an image of fire as a living creature, preserved in the Polish folk culture. This image is corroborated by linguistic data, e.g. names, epithets, established connections, riddles, proverbs, formulas of greeting and bidding farewell to a home fire and of obviating fire, as well as by “paralinguistic data” that is beliefs and practices. Conceptualization of natural phenomena (such as fire) in the categories of a living “being” has a general cultural character, corresponds to a vision of the world as an integrated organism whose components are endowed with life and consciousness, and can be a manifestation of the mythical perception of the world. The analysed material has been acquired from dictionaries of dialects, works of folklore collectors and archive resources (i.e. the Ethnolinguistic Archive of Maria Curie-Skłodowska University and the File of the Dictionary of Polish Dialects of the Polish Academy of Sciences).
Keywords: ethnolinguistics; linguistic view of the world; fire as a living creature